A QUALITATIVE STUDY OF BLACK WOMEN’S EXPERIENCES WITH EXCLUSIONARY DISCIPLINE IN K-12 AND ITS IMPACT - (:unkn) unknown (My University, 2025)
A growing body of literature highlights Black girls’ experiences with exclusionary discipline during K-12 education. Yet, less of this work explores how these experiences shape their lives into adulthood. Using Black feminist thought, the semi-structured interviews and sister circle for this study centered the unique K-12 experiences of 11 Black women to understand how their experiences with exclusionary discipline as youth have shaped their lives. Four themes emerged including They Tried to Tell Me Who I Was Before I Knew Who I Was, Nothing You Say Matters So Why Say Something, It’s Because WE Have To, and Y’all Are My Sisters. The findings highlight that Black women’s unique experiences with exclusionary discipline occur at the intersection of race and gender and can shape their lives into adulthood; the findings illustrate such impacts on their mental and emotional well-being such as anxiety, low self-esteem, and self-doubt. The findings also highlight how these Black women, when sharing their experiences within a sister circle are emotionally supported, can have their experiences validated, and can establish a sense of community and belonging. Researchers, policy makers and teachers can utilize this study to increase their awareness of the unique needs of Black girls and women given that research consistently documents the importance of providing Black women and girls the space to bring meaning to their own experiences with K-12 school policies and practices.
Keywords: Educational philosophy